Newborn blood spot screening – knowledge of genetic testing among mothers - David, Angeline; Cruz, Meredith O.; Telega, Grzegorz; Simpson, Pippa; Pan, Amy; Nagórska, Małgorzata (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Newborn blood spot screening (NBS) uses genetic technology to screen for selected genetic, endocrine, and metabolic disorders. The purpose of the study was to assess the knowledge of newborn blood spot genetic screening among expectant mothers. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Between October 2015 and January 2016, a 20 question, multiple-choice questionnaire was administered to expectant mothers presenting for a pre-natal ultrasound at the Maternal Fetal Care Center in Milwaukee, Wisconsin Froedtert Hospital. Statistical analysis used Chi-Square or Fisher’s exact test for categorical variables. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. 103 women completed the survey; 34% believed that education regarding screening is incomplete and 39% believed that it needs improvement. 27% knew the purpose of newborn screening. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Many mothers lack general and specific knowledge about NBS and the diseases screened for. Health education that provides accurate and complete information on the newborn blood spot screening should be provided to all parents prior to the administering of any genetic testing. Key areas that should be targeted include: purpose of NBS, screened diseases and how to interpret the results of the test.